IMPLEMENTATION OF ABSORPTION WELLS IN ORGANIC WASTE PROCESSING IN KAMASAN VILLAGE, BANJARAN DISTRICT, BANDUNG REGENCY - Ridho Rinaldi; Zidan Maula Fatih; Bintang Rizqia; Dika Septiani; Radinda Putri; Ghifari Naufal; Raka (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Kamasan Village, Bandung Regency, was known as a flood-prone area from 2012 to 2020. Although flood mitigation efforts have successfully reduced flooding since early 2020, household waste management, particularly organic waste, remains a major challenge. This study examines the implementation of biopore infiltration wells with a diameter of 11 cm and a depth of 1 meter that utilize media from processed organic waste as a filtration layer. This system not only aims to increase the rate of water infiltration and reduce runoff but also utilizes household organic waste as an integrated solution. In addition, this study also examines the impact of infiltration well implementation on community awareness of organic waste management. Initial observations indicate that the use of organic waste media has been shown to increase soil absorption capacity without producing leachate. This model has the potential to be an effective local solution for groundwater conservation and sustainable waste management, while simultaneously increasing active community participation.